The Influence of Enterprise Resource Planning on Firm Value Mediated Financial Performance in State-Owned Commercial Banks - Idrus, Arifin (International Journal of Artificial Intelligence Research, 2023)
The development of technology and information greatly influences the progress of the business world. Various types of companies have adopted technology to improve company performance so they can compete and maintain business continuity in the future. This research aims to examine the influence of Enterprise Resource Planning (ERP) and financial performance on company value. This research uses a sample of state-owned banks registered on the IDX during the period 2015 to 2022. The sampling technique is purposive sampling by obtaining 4 state-owned banks multiplied by 8 years, namely 32 observation data. The data analysis method in this research is  Structural Equation Modeling Partial Least Square (SEM-PLS) method with the help of SmartPLS 4.0 software. The research results show that ERP partially has a positive and significant effect on financial performance (NPM), and company value, and financial performance has a positive and significant effect on company value. Another finding is that financial performance is able to mediate the relationship between Enterprise Resource Planning (ERP) and company value by 0.116% and 11.6%